Bacteriological profile of urinary tract infections at a tertiary care hospital in Western Uttar Pradesh, India - Singh, Vijay Prakash; Mehta, Abhishek (International Journal of Research in Medical Sciences, 2017)
Background: This prospective study was intended to identify the bacterial pathogens causing urinary tract infections and their antimicrobial resistance patterns in a tertiary care teaching hospital of Western Uttar Pradesh, India. Methods: Clean-catch mid-stream urine samples were collected from patients symptomatic for UTI. Samples were cultured aerobically on CLED agar and strains having significant growth (>105cfu/ml) were further processed for identification using standard microbiological techniques and their antimicrobial susceptibility pattern evaluated by Kirby Bauer disk diffusion as per CLSI guidelines. Results: Out of the 2250 urine samples processed, 750 showed significant growth on aerobic culture. Thus, the prevalence of UTI in the population was 33.3%. E. coli was the commonest isolate (33.3%) followed by S. aureus (20 %), Klebsiella spp. (13.3%), Coagulase Negative Staphylococci (13.3%), Enterococcus spp. (6.7%), Pseudomonas spp. (6.7%) and Candida spp. (6.7%). Amongst these isolates, Gram negative bacilli have shown a high susceptibility to imipenem, levofloxacin, nitrofurantoin, linezolid and amoxyclav and Gram positive organisms towards levofloxacin, nitrofurantoin, linezolid, vancomycin and amikacin. Conclusions: This study has shown nitrofurantoin and fluoroquinolones to be the most effective drugs for the empirical therapy of UTI in our region. The study of antimicrobial susceptibility pattern of UTI in a particular area can guide the clinicians in the rational choice of antibiotic treatment so that misuse of antibiotics can be prevented.